Leonora Unbound: Tonality as Allegory - Dineen, Murray (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
Tonality has both a literal and a figurative or allegorical aspect. Tonal unity, a commonplace among much current music theory, is a superficial entity, a literal facade beneath which lies a sustained and discursive domain, where tonality is made and remade in a continual process of fracturing and reinterpretation. Like the frought persona of Beethoven's Leonora-cum-Fidelio, the tonality of the aria "Abscheulicher! ... Komm Hoffnung ..." defies analysis as a unified structural whole. Like the behaviour of the piano teacher in Bonnie Burnard's short story "Music Lessons," the conventional behaviour of tonality can be seen to crack and buckle in the aria, albeit only briefly, before it is smoothed over and fractious elements suppressed behind a facade of the calibre of a Fidelio.